Local Government and the Constitution: The Nigerian Experience - Salami, Adebayo T. (NIU Journal of Social Sciences, 2022)
What is or should be the research relationship between local government and the constitution? How can the research relationship be explored? What should be the investigative parameters and criteria? Put more directly, what form of relationship exists or should exist between local government and the constitution? How can the relationship be investigated? Of more fundamental necessity, is there any justification to investigate the relationship? Consequently, of what relevance is the study of the relationship to scholarship? The questions are crucial to both the understanding of the theory and practice of federalism and to the specialty, local government studies in Nigeria in particular. Apart from assisting in creating scholarly avenues for a profound study of power interplays in federally organized systems, part of the objectives of the paper is to as well place the Nigerian experience under close scrutiny and perhaps use it to generate issues and problems of comparative research that would in turn impact tremendously on generalization and theory building within the sub-field and specialty. Data sources are secondary and this can be justified by the nature of the research topic and the attendant core/research questions. The mode of analysis is descriptive, qualitative, historical and philosophical. Keywords: Local Government, Constitution, Nigerian Experience.